Research on OSU based M-OTN technology innovation and application - Yadong GONG; Ruiquan JING; Heng ZHOU; Junjie LI; Xiaoli HUO (Dianxin kexue)
With SDH and MSTP networks facing withdrawal from the network, OTN will replace SDH/MSTP networks and sink to the edge of the network.At the same time, the requirements of customers’ services are also changing rapidly, but the packet enhanced OTN has various problems and challenges in carrying these services.Therefore, the M-OTN technology system based on OSU was proposed, and the technical advantages of M-OTN/OSU were comprehensively analyzed by combining its technical essence and experimental data.The results show that M-OTN/OSU has obvious advantages over packet enhanced OTN technology in many aspects.The application and deployment of M-OTN/OSU in the field network and network evolution are of great concern.Combined with the technical characteristics of M-OTN/OSU and the deployed devices in the field network, the research of M-OTN/OSU in networking scheme and network evolution strategy was shared.